Identification of tumor endothelial cells with high aldehyde dehydrogenase activity and a highly angiogenic phenotype. - Hitomi Ohmura-Kakutani; Kosuke Akiyama; Nako Maishi; Noritaka Ohga; Yasuhiro Hida; Taisuke Kawamoto; Junichiro Iida; Masanobu Shindoh; Kunihiko Tsuchiya; Nobuo Shinohara; Kyoko Hida (PLoS ONE, 2014)
Tumor blood vessels play an important role in tumor progression and metastasis. It has been reported that tumor endothelial cells (TECs) exhibit highly angiogenic phenotypes compared with those of normal endothelial cells (NECs). TECs show higher proliferative and migratory abilities than those NECs, together with upregulation of vascular endothelial growth factor (VEGF) and VEGF receptor 2 (VEGFR2). Furthermore, compared with NECs, stem cell markers such as Sca-1, CD90, and multidrug resistance 1 are upregulated in TECs, suggesting that stem-like cells exist in tumor blood vessels. In this study, to reveal the biological role of stem-like TECs, we analyzed expression of the stem cell marker aldehyde dehydrogenase (ALDH) in TECs and characterized ALDHhigh TECs. TECs and NECs were isolated from melanoma-xenografted nude mice and normal dermis, respectively. ALDH mRNA expression and activity were higher in TECs than those in NECs. Next, ALDHhigh/low TECs were isolated by fluorescence-activated cell sorting to compare their characteristics. Compared with ALDHlow TECs, ALDHhigh TECs formed more tubes on Matrigel-coated plates and sustained the tubular networks longer. Furthermore, VEGFR2 expression was higher in ALDHhigh TECs than that in ALDHlow TECs. In addition, ALDH was expressed in the tumor blood vessels of in vivo mouse models of melanoma and oral carcinoma, but not in normal blood vessels. These findings indicate that ALDHhigh TECs exhibit an angiogenic phenotype. Stem-like TECs may have an essential role in tumor angiogenesis.